Pengaruh Core Stability Excercise Terhadap Keseimbangan Dinamis Pemain Sepak Bola Syarekah Jaya Usia 12-15 Tahun - Bagus Abdul Rozaq; Nurul Halimah; Puspo Wardoyo; Angria Pradita (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: Dynamic balance is an ability that must be possessed by football players, especially in terms of improving player performance during matches and reducing the risk of injury to the lower limbs. One way to improve dynamic balance is with core stability exercise.Methods: This study is a pre-experimental study to determine whether there is an increase in dynamic balance by providing core stability exercise to football players. The research design used in this study was a one group pretest – posttest design. This research was conducted on football players aged 12 -15 years at SSB Syarekah Jaya. Core stability exercise was given 12 times, and dynamic balance was measured using the Y balance test. Measurement of dynamic balance with the Y Balance Test is carried out in three different directions, namely towards the front (anterior), towards the back middle (posteromedial), and towards the back and outer side (posterolateral). The core stability exercises given are plank, side plank, curl up and bridging. The frequency of exercise given is 3 times a week for four weeks with an intensity of 10 repetitions per set, and held for 5 seconds. Posttest data retrieval was carried out again for all players after undergoing core stability exercise training 12 times using the Y Balance Test..Results: The composite value of Y Balance Test on posttest results after giving 12 times of core stability exercise is quite significant compared to the results of pretest before giving core stability exercise. The data was tested for normality using the Saphiro-Wilk test with the results obtained were P>0.05, which means the data were normally distributed. The researcher then tested the hypothesis using paired t-test and got P <0.05 and the IK did not pass zero, which means that there is a difference in the average composite value of balance before and after giving core stability exercise.Conclusion: The results obtained in the study showed an increase in dynamic balance in football players after being given core stability exercise.